Cross-case synthesis - Sian Sullivan; Michèle Baussant; Lindsey Dodd; Olivette Otele; Irène Dos Santos (Conserveries Mémorielles)
The project ‘Disrupted Histories, Recovered Pasts’ forming the focus of this Special Issue has researched biographical experiences that have undergone a rupture as a result of brutal political, social and/or economic changes, linked especially with war, colonization/decolonization, migration and exile. These personal biographical experiences have tended to find themselves on the margins of national and/or academic historical narratives. In this final paper of our Special Issue we share the open-ended process of co-production, cross-case learning, and synthesis that accompanied case research, focusing especially on our systematic cross-case engagement, which involved sharing and theorising content and experiences across our case-studies, and the commonalities and differences we identified across our case-studies through this process. We outline the steps we took in this process to sharing what we know, find ‘points of articulation’ across our case-studies and to identify themes emerging across our research.